Comparison of microhardness of three interim restorative materials: PEEK, PMMA and indirect composite - Ansari, Parinaz; Nourbakhsh, Mehran; Koosha, Sara (Journal of Dental School, 2021)
Objectives Interim restorations play a critical role in success of restorative treatments. However, they need to preserve their integrity in the oral environment. Microhardness is an important factor in preservation of the integrity of restorations. This study aimed to compare the microhardness of three interim restorative materials namely polyether ether ketone (PEEK), an indirect composite, and polymethyl methacrylate (PMMA). Methods This in vitro, experimental study evaluated 10 disc-shaped specimens, measuring 15 mm in diameter and 1 mm in thickness, fabricated from PEEK, an indirect composite, and PMMA. The microhardness of the specimens was measured at three points of each specimen using the Vickers’ hardness test before and after water storage for 30 days. Data were analyzed using repeated measure ANOVA, one-way ANOVA and Tukey’s test. Results Indirect composite showed maximum microhardness, which was significantly higher than that of the other two materials (P=0.001). However, no significant difference was noted in microhardness of PEEK and PMMA (P=0.33). The microhardness of the materials did not significantly change after 30 days of water storage (P=0.06). Conclusion The microhardness of indirect composite was higher than that of PEEK and PMMA. Also, 30 days of water storage had no significant effect on microhardness of the materials.